2021
DOI: 10.54957/jurnalku.v1i3.40
|View full text |Cite
|
Sign up to set email alerts
|

Peran Komisaris Independen Di Indonesia : Multinationality, Tax Haven, Penghindaran Pajak

Abstract: Penelitian ini bertujuan untuk menguji pengaruh multinationality dan tax haven terhadap penghindaran pajak. Selain itu, penelitian ini juga memasukkan komisaris independen sebagai pemoderasi daalam hubungan variabel independen dan dependen. Penelitian ini menggunakan data perusahaan sektor industri barang konsumsi tahun 2017 sampai dengan 2019 yang bersumber dari www.idx.co.id. Berdasarkan purposive sampling, sampel final penelitian ini berjumlah 64 observasi. Metode analisis yang digunakan dalam penelitian in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…It can be concluded that H0 is rejected and H4 is accepted, namely the tax haven country utilization variable has an effect on tax aggressiveness. The results of this study are in line with research conducted by Pramudya, et al (2021) which states that tax haven country utilization has a negative and significant effect on tax avoidance. However, it is not in line with research conducted by Septiani & Winata (2022) which states that tax haven country utilization has no effect on tax aggressiveness.…”
Section: Effect Of Thin Capitalization On Tax Aggressivenesssupporting
confidence: 90%
See 1 more Smart Citation
“…It can be concluded that H0 is rejected and H4 is accepted, namely the tax haven country utilization variable has an effect on tax aggressiveness. The results of this study are in line with research conducted by Pramudya, et al (2021) which states that tax haven country utilization has a negative and significant effect on tax avoidance. However, it is not in line with research conducted by Septiani & Winata (2022) which states that tax haven country utilization has no effect on tax aggressiveness.…”
Section: Effect Of Thin Capitalization On Tax Aggressivenesssupporting
confidence: 90%
“…The results that show a negative effect on the use of tax haven countries as a tool of tax aggressiveness indicate that companies that have subsidiaries in tax haven countries tend not to commit acts of tax aggressiveness. Aryotama (2019) in Pramudya (2021) states that multinational companies that have subsidiaries in tax haven countries are not intended as a tax avoidance tool but rather to gain a larger market share and an easier workforce. This is done by the management of a company in creating a longer company survival.…”
Section: Effect Of Thin Capitalization On Tax Aggressivenessmentioning
confidence: 99%
“…Including independent commissioners in the corporation can provide better control of the directors' performance. The higher the number of independent commissioners in a corporation, the more probable the oversight will be stricter to prevent tax avoidance (Aulia et al, 2018;Pramudya et al, 2021;Sunarsih & Handayani, 2018). Independent commissioners are expected to reduce tax avoidance activities by managers to increase compensation as company executives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, the percentage of the board of commissioners in a company indirectly affects tax management. Aulia et al (2018), Eksandy (2017), Pramudya et al (2021), Sunarsih & Handayani (2018), and Wijayanti & Merkusiwati (2017) suggested that the independent commissioner is negatively associated with tax avoidance. Rahma & Firmansyah (2022) found that an independent commissioner can strengthen the negative effect of companies with more significant debts in reducing tax avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Managers prioritize market expansion and future corporate survival over potential tax savings through profit transfers to affiliate companies in lowtax rate countries. This decision shows managers' focus on the long-term growth and stability of the company rather than solely on the short-term gains obtained from aggressive taxation strategies (Pramudya et al, 2021).…”
Section: The Effect Of Utilization Of Tax Haven Countries On Profit-s...mentioning
confidence: 99%